Technical, commercial, and regulatory challenges of QoS : - Xiao, XiPeng (Elsevier / Morgan Kaufmann, 2008)
This book provides a comprehensive examination of Internet QoS theory, standards, vendor implementation and network deployment from the practitioner's point of view, including extensive discussion of related economic and regulatory issues. Written in a technology-light way so that a variety of professionals and researchers in the information and networking industries can easily grasp the material. Includes case studies based on real-world experiences from industry.